Greater adolescent cognitive ability is linked to lower risk of cognitive impairment in later life. (31st December 2021) - Gruenewald, Tara L; Arpawong, Thalida Em; Zavala, Catalina; Grossman, Molli; Walters, Ellen E; Peters, Kelly; Lapham, Susan; Manly, Jennifer J; Gatz, Margaret; Prescott, Carol Arlene
Abstract: Background: There have been few investigations of the role that adolescent cognitive ability might play in predicting who will later develop cognitive impairment. This is due, in part, to a lack of cohorts with early‐life cognitive assessment who have been followed to later adulthood. We capitalized on the 1960 Project Talent high school cohort to assess whether higher adolescent cognitive ability predicted lower risk of impaired cognitive function in older adulthood. A subsample of twin and non‐twin siblings allowed for assessment of whether these associations are due to shared family and genetic factors. Method: Data come from the 1960 Project Talent (PT) baseline data collection (n>360, 000) and two follow‐ups: the Project Talent Twin & Sibling (PTTS; n=2, 491) Study and the Project Talent Aging Study (PTAS; n=6, 421). The 1960 data collection assessed performance in multiple cognitive abilities (see Table 1). In 2018, participants/proxies reporting 2 or more symptoms of cognitive impairment on the AD8 Dementia Screener were classified as having a positive screen. Binary logistic generalized estimating equations assessed odds of a positive AD8 screen as a function of 1960 cognitive abilities. Models included age, race, sex, adolescent family SES, and adult educational attainment covariates. Co‐sibling control models examined whether associations remained when accounting for shared family and genetic characteristics. Results: Covariate‐adjusted models indicated that each 1 SD higher adolescent cognitive ability predicted lower odds of a positive AD8 screen in later life for most ability domains (e.g., general cognitive ability OR = 0.86 (95% CI = 0.76, 0.98), see Table 1); associations were attenuated somewhat with inclusion of adult educational attainment in models. Preliminary co‐sibling control analyses indicated the persistence and strengthening of this association (OR = 0.57 (95% CI = 0.36, 0.91)). Conclusion: Findings indicate that greater performance in multiple cognitive domains in adolescence predicts lower risk of cognitive impairment over 5 decades later. A co‐sibling control analysis indicated that the link between adolescent general cognitive ability and later‐life cognitive impairment is not simply due to shared family background and genetic factors. Ongoing analyses are assessing whether this is true for other cognitive domains and other indicators of cognitive function.